Differences in endogenous hormones levels and mineral nutrient contents between seedy and seedless Orah mandarins during the flower and fruit abscission stages - DONG Jianmei; LI Jing; YANG Di; LI Jinxue; LAI Xinpu; LIU Hongming; FU Xiaomeng; YANG Hongxia; DU Yuxia (Guoshu xuebao)
[Objective] The seedless Orah mandarin represents a novel cultivar derived from the seedy Orah mandarin via radiation-induced mutagenesis. This seedless variant exhibits a propensity for floral and fruit abscission, resulting in diminished yield during cultivation. The lack of clarity regarding the physiological alterations occurring throughout the flowering and fruiting phases of the seedless Orah mandarin complicates efforts to effectively preserve its flowers and fruits. This study sought to examine the variations in mineral nutrient and endogenous hormone contents between seedy and seedless Orah mandarins during the flowering and fruiting stages. Additionally, it aimed to identify the primary factors influencing flower and fruit drop in seedless Orah mandarins, with the objective of providing theoretical support for the protection of flowers and fruits in seedless Orah mandarins. [Methods] In this study, three-year-old Orah mandarin trees, both seedy and seedless, grafted onto Fragrant Citrus rootstocks, were utilized as experimental materials. Representative specimens exhibiting moderate and consistent tree size, growth vigor and flower amount were selected for analysis. Samples of flowers, fruits, spring leaves and fall leaves were collected at ten-day intervals commencing from the full bloom period. The spring and fall leaves were subsequently analyzed to determine their concentrations of nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), iron (Fe), manganese (Mn), copper (Cu) and zinc (Zn). Flowers, fruits and spring leaves were analyzed to determine the contents of auxin (IAA), gibberellin (GA3), abscisic acid (ABA), zeaxanthin nucleoside (ZR) and jasmonic acid (JA-me). Subsequently, a correlation analysis was conducted. [Results] IAA content in seedless Orah mandarin leaves was significantly lower than that in seedy Orah mandarin leaves from 20 to 30 days post-flowering. Similarly, the IAA content in seedless Orah mandarin flowers and fruits were lower than those in seedy Orah mandarins from 10 to 40 days post-flowering, but higher on the 50th day. The GA3 content in the leaves of seedless Orah mandarin was observed to be lower than that in seedy Orah mandarin over the period of 10 to 40 days. Similarly, the GA3 content in the flowers and fruits of seedless Orah mandarin were found to be lower than those in seedy Orah mandarin between 20 and 50 days. Additionally, the ABA content in the leaves of seedless Orah mandarin consistently remained lower throughout the entire observation period. In the context of flowers and fruits, ABA levels in seedless Orah mandarins exhibited a significant increase on the 30th day, surpassing the levels recorded in the same cultivar on earlier days. Conversely, no significant variation was detected in the ZR content of flowers and fruits between seedy and seedless Orah mandarins. Furthermore, the JA-me content in leaves, flowers and fruits showed a gradual decline starting from the full-bloom period. There was no statistically significant difference in JA-me content between seedy and seedless Orah mandarins from day 10 to day 40. The JA-me content in seedless Orah mandarin was notably higher than that in seedy Orah mandarin on the 50th day post full bloom. The (Zr+GA3+IAA)/ABA ratio demonstrated a progressive increase in leaves, flowers and fruits. However, a significantly lower ratio was recorded in seedless Orah mandarin compared to seedy Orah mandarin on the 30th day. During the early stages of development, the contents of nitrogen (N), phosphorus (P) and potassium (K) increased in both seedy and seedless Orah mandarin leaves. Conversely, a gradual decline in these nutrient levels was observed during the later stages of the flowering period. In the early growth stage, the contents of nitrogen, phosphorus, and magnesium (Mg) in the spring leaves of the seedless Orah mandarin were found to be lower compared to those in the seedy Orah mandarin. However, during the later growth stage, these nutrient levels were higher in the seedless variety. Conversely, the calcium (Ca) content in the autumn leaves of the seedless Orah mandarin exceeded that of the seedy variant, whereas in the spring leaves, the Ca concentration was lower in the seedless Orah mandarin compared to the seedy counterpart. The concentrations of phosphorus, potassium, calcium and magnesium in the autumn leaves of seedless Orah mandarin were higher than those observed in the same leaves of seedless Orah mandarin. In contrast, the concentrations of iron (Fe), manganese (Mn), copper (Cu) and zinc (Zn) were lower in the autumn leaves of seedless Orah mandarin compared to the same reference. Furthermore, a significant positive correlation was identified among the ABA, ZR and JA-me contents in the leaves, flowers and fruits of mandarins. Furthermore, a notable positive correlation was identified in the JA-me content of seedless Orah mandarin. A significant positive correlation was also observed among the concentrations of potassium, manganese and copper in the leaves during both spring and autumn. [Conclusion] The principal cause of flower and fruit drop was determined to be the low concentrations of IAA and GA3 observed during the early developmental stages. The initial physiological fruit drop can be attributed to the combined effects of reduced IAA and GA3 levels and increased ABA and JA-me concentrations. Furthermore, significant variations in mineral nutrient contents existed between seedless and seedy mandarin varieties. From a production standpoint, it is advisable to supplement nitrogen fertilizer before the flowering stage, while phosphorus and potassium fertilizers should be applied in appropriate amounts. For seedless Orah mandarins, it is recommended to apply calcium fertilizer and trace elements through foliar spraying during the flowering period.